2008
DOI: 10.1016/j.expneurol.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal neurotransmitter conditioning restores the functional activity of adult spinal cord neurons in long-term culture

Abstract: The ability to culture functional adult mammalian spinal-cord neurons represents an important step in the understanding and treatment of a spectrum of neurological disorders including spinal cord injury. Previously, the limited functional recovery of these cells, as characterized by a diminished ability to initiate action potentials and to exhibit repetitive firing patterns, has arisen as a major impediment to their physiological relevance. In this report we demonstrate that single temporal doses of the neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…This supports the view that mature SCMNs are strongly dependent on their interactions with neurotrophins, cAMP, and soluble factors from their target tissue. A similar trophic dependence of mature SCMNs has also been described by Das et al ( 27,28 ) . Adult rat SCMNs survive in the presence of a complex cocktail of neurotrophins ( 27 ) and they reach electrical functionality in the presence of neurotransmitters ( 28 ) .…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…This supports the view that mature SCMNs are strongly dependent on their interactions with neurotrophins, cAMP, and soluble factors from their target tissue. A similar trophic dependence of mature SCMNs has also been described by Das et al ( 27,28 ) . Adult rat SCMNs survive in the presence of a complex cocktail of neurotrophins ( 27 ) and they reach electrical functionality in the presence of neurotransmitters ( 28 ) .…”
Section: Introductionsupporting
confidence: 50%
“…However, other molecules may be involved in the survival of SCMNs. For instance, Das et al ( 27,28 ) showed that a more complex mixture of factors (BDNF, GDNF, neurotrophin-3, heparin sulfate, cardiotrophin-1, vitronectin, and acidic fi broblast growth factor) is necessary for the maintenance of adult SCMNs under their conditions.…”
Section: Feeding Of Motor Neuron Culturesmentioning
confidence: 98%
See 1 more Smart Citation
“…A timed application of a limited number of growth factors to the culture medium substantially enhanced cell survival, as opposed to prolonged application. Our research shows that neurons cultured using this technique retain their phenotypic properties (Das et al, 2008). The use of synthetic substrates, such as DETA, allows for reproducible and precise quantification of the culture substrate properties.…”
Section: Introductionmentioning
confidence: 97%
“…Surface modification with SAMs is also compatible with advanced photolithography methods[30, 34]. Studies have also shown that cells survive on these surfaces for extended periods of time[35, 36], do not migrate off the patterned areas[34] and exhibit the typical morphology and physiology of the specific cell type[16, 37]. …”
Section: Introductionmentioning
confidence: 99%